MORPHOFUNCTIONAL STATE OF THE SKIN IN WOMEN DURING GESTATION AND LACTATION AND ITS PROGNOSTIC VALUE FOR ASSESSING NEWBORN STATUS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This review presents a comprehensive analysis of the morphofunctional changes in the skin and its appendages within the "mother-child" system during gestation, lactation, and early postnatal maturation. The study examines physiological transformations driven by endocrine and immunological restructuring (hyperpigmentation, connective tissue alterations, vascular and glandular reactions), as well as specific dermatoses of pregnancy (atopic eruption of pregnancy, polymorphic eruption of pregnancy, pemphigoid gestationis, and intrahepatic cholestasis). Particular emphasis is placed on the dynamics of biophysical skin barrier parameters, including transepidermal water loss (TEWL), pH levels, and stratum corneum hydration. Based on current data, a high degree of autonomy in the formation of the neonatal epidermal barrier is demonstrated. The review underscores the necessity of a multidisciplinary approach to patient management to ensure the dermatological health and psycho-emotional well-being of both mother and child.
Keywords: pregnancy, mother-child system, specific dermatoses of pregnancy, morphofunctional skin state, transepidermal water loss (TEWL), skin barrier function, newborn skin, melasma, intrahepatic cholestasis of pregnancy.